Kombinasi Herbal Steam Bath dan Massage Terapi pada Ibu Nifas dalam Mencegah Post Partum Blues - Kristina Maharani; Choirul Anwar; Agus Suwandono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to analyze the effectiveness of a combination of herbal steam bath and massage therapy as a way to prevent post partum blues of postpartum mothers. This type of quasi experiment research design with pre-test and post-test control group. The results of the study, herbal steam bath and massage therapy are more effective than conventional puerperal care in the prevention of post partum blues with a p-value <0.05. Conclusion, Herbal steam bath and massage therapy can be used as an alternative therapy in the prevention of post partum blues. Keywords: Herbal Steam Bath, Massage therapy, Postpartum Blues, Postpartum Blues